STRATEGIC MANAGEMENT OF MADRASAH ALIYAH IN IMPROVING EDUCATION QUALITY: A Descriptive-Analytical Study At Man 2 Jembrana, Bali - Arjiman, Arjiman (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
This research on the strategic management of Madrasah Aliyah Negeri (MAN) 2 Jembrana examines and analyzes: (1) the formulation of strategic management, which includes: (a) the formulation of vision, mission, and objectives, and (b) the concept and implementation of the Madrasah Aliyah education system; (2) the implementation of strategic management, highlighting the leadership of the Madrasah principal based on his fundamental skills; and (3) the evaluation of strategic management in efforts to improve the quality of education. The main research problem focuses on: “How is strategic management at Madrasah Aliyah Negeri 2 Jembrana applied to improve the quality of education in Bali Province?” Meanwhile, the purpose of this study is to determine: “What constitutes effective strategic management in improving education quality through the application of a conducive strategic management system at Madrasah Aliyah Negeri 2 Jembrana.” This study employed a qualitative descriptive approach. Data collection techniques included observation, interviews, and document analysis. The findings indicate that the strategic management of Madrasah Aliyah in improving education quality at Madrasah Aliyah Negeri 2 Jembrana needs to be maintained, enhanced, and further developed in the following aspects: (1) analysis of both external and internal stakeholder needs; (2) planning, which involves: (a) the formulation of vision, mission, and objectives, and (b) the formulation of educational concepts through thorough preparation before program implementation; (3) implementation of concepts and programs carried out with sound management supported by the principal’s skills in managing Madrasah resources; strict recruitment of human resources complemented by systematic and well-planned HR development; and high-quality teachers and educational outcomes, particularly reflected in the achievements of MAN 2 Jembrana students; and (4) structured and systematic evaluation with proper management mechanisms, enabling evaluation to serve as a tool for assessing and measuring the implementation of educational programs.